2008
DOI: 10.1111/j.1468-2982.2008.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Signs of Temporomandibular Disorders Stable and Predictable in Adolescents With Headache?

Abstract: The aim of the present study was to study changes in signs and symptoms of temporomandibular disorders (TMD) and factors predicting TMD signs in adolescents with and without headache. A population-based sample (n = 212) of 13-year-olds with and without headache was re-examined at the age of 16. The study included a questionnaire, face-to-face interview and somatic examination. In addition, a neurological examination, a muscle evaluation and a stomatognathic examination were performed. Significant changes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…Crackling may occur due to degenerative disc problems, with the leakage of synovial fluid between the supra and infra disc compartments16, 26 ) . In the present study, joints noises were presented by clicking in 82.4% of the participants with TMD, which is in agreement with studies reporting this to be a frequent sign of this disorder7, 29 ) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Crackling may occur due to degenerative disc problems, with the leakage of synovial fluid between the supra and infra disc compartments16, 26 ) . In the present study, joints noises were presented by clicking in 82.4% of the participants with TMD, which is in agreement with studies reporting this to be a frequent sign of this disorder7, 29 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Numerous clinical conditions, such as poor posture, malocclusion and bruxism (teeth clenching/grinding), may be related to the muscles of mastication, the temporomandibular joint and associated structures, giving rise to TMD2 ) . The literature also suggests that occlusal abnormalities may be causes of headache, TMD and facial pain6, 7 ) and may affect facial growth and esthetics, leading to a tendency toward either vertical or horizontal facial growth (long face or short face pattern, respectively)8 ) . Our research group previoulsy showed that the occurrence of headache in children and adolescentes with signs/symptoms of TMD is frequent, regardless of gender and intensity of signs and symptoms of TMD9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on adolescents also found associations between the prevalence of TMD and sex, 9,12,43 and an association between pubertal development and TMD pain both in boys and in girls has been observed. 43 Girls seem to be more likely to report HAs compared with boys 15,23,29,43,44 and it is speculated that a combination of developmental and hormonal changes would be responsible for increasing HAs in girls after menarche.…”
Section: Discussionmentioning
confidence: 84%
“…10,11 HA prevalence rates of up to 51% have been reported in children/adolescents. 11 The relationship between HA and TMD is not predictable, 12 but HA are one of the most commonly associated conditions observed in children and adolescents diagnosed with TMD. [13][14][15][16] Moreover, signs and symptoms of TMD occur more often in adolescents with HA in comparison with those who are HA-free.…”
mentioning
confidence: 99%
“…However, this relationship has not always been investigated or described (19) and some studies have only cited age as exerting an influence on the association between these clinical conditions (20,21). Nevertheless, a recent large study by Tecco et al reported a significant association between TMD/headache and patient characteristics, such as female gender, young age, and the presence of posterior unilateral crossbite (22).…”
Section: Discussionmentioning
confidence: 99%